The use of video games and issues of aggressive behavior among pre-adolescent students - Tzivani, Maria; Gazi, Angeliki (Psychology: the Journal of the Hellenic Psychological Society, 2025)
The aim of this research is to investigate the relationship between the use of video games and aggressive behavior among students of the fifth and the sixth grade of primary school. The sample consisted of 225 students. Data study were collected via an anonymous self-report questionnaire, which integrated questions regarding socio-demographic characteristics, gaming frequency, as well as the elements of the Game Addiction Scale for Adolescents (Lemmens et al., 2009) and the Peer Conflict Scale (PCS; Marsee & Frick, 2007). Based on frequencies and relative frequencies calculated, results revealed that, on average, students play video games eight hours per week. It was found that, depending on the cut-off point, a percentage of 0.9% to 11.1% is addicted to video games. In terms of gaming frequency, boys scored significantly higher than girls. Βoys also scored significantly higher on every sub-factor of addiction scale, as well as on every aggression sub-factor. It was found that, for the total sample, the correlations of every individual factor of addiction and aggression were statistically significant. The pattern of results was similar for the correlations between gaming frequency and aggression, but with weaker correlation coefficients. Furthermore, when predicting both overt and relational aggression from the other variables, addiction emerged as the most consistent predictor. Finally, mediation analyses indicated that addiction (a) mediates the relationship between gaming frequency and aggression, and (b) mediates the relationship between gender and aggression.